Serum Cystatin C as an Endogenous Marker of Renal Function in Patients with Chronic Kidney Disease (CKD) - Faraji, Md Anwarul Haque; Anwar, Mohammed Rashed; Debnath, Dilip Kumar; Alam, Md Babrul; Morshed, Syed Mahbub; Hasan, KAM Mahbub (Journal of Current and Advance Medical Research, 2018)
Background: Cystatin C is being considered as a potential replacement for serum creatinine as a filtration marker. Objectives: This present study was conducted to determine the validity of Cystatin C as a renal function test and to compare the Cystatin C and serum creatinine level between the CKD cases and person not having CKD. Methodology: The present case control study was conducted in the department of Nephrology of Dhaka Medical College Hospital during the period of January 2009 to December 2009 with the aim to find out the serum Cystatin C as diagnostic markers of chronic kidney disease. In the present study total 100 respondents were included. Among them 50 were CKD patients and another 50 were without CKD. Results: It was an age and sex matched study. Out of 50 patients with CKD, 29 (58.0%) were in the stage IV followed by 15 (30.0%) were in the stage III and rest 6 (12.0%) were in the stage V. In CKD group 31 (62.0%) had glomerulonephritis, 18 (36.0%) had HTN, 11 (22.0%) had DM and 3 (6.0%) had obstructive uropathy. In without CKD group 9 (18.0%) had HTN, 6 (12.0%) had DM. Mean±SD of Serum Creatinine in CKD and without CKD groups were 5.73±2.69 and 0.85±0.11mg/dl respectively. Mean±SD of Serum Cystatin C in CKD and without CKD groups were 3.59±1.21 and 0.71±0.09 mg/dl respectively. In all patients sensitivity of Cystatin C to diagnose CKD was 100.0% and specificity also100.0%. Sensitivity of serum creatinine to diagnose CKD was 88.0% and specificity was 100.0%. Conclusions: Cystatin C proved more reliable than creatinine and was comparable to plasma creatinine and Cockcroft-Gault estimation. Serum Cystatin C had higher diagnostic accuracy with high sensitivity and specificity to detect renal function and is a reliable marker of renal function. Journal of Current and Advance Medical Research 2017;4(1):3-12